Implementation and Evaluation of a Long-Term Care at Home (Home LTC) Service in a Rural Community Pharmacy Setting - Megan Ditzman; Stevie Veach; Jessie Schaefer; Kaitlin Luett; Bryan Kendall; Matthew Witry (INNOVATIONS in Pharmacy)
Background: The majority of older Americans are expected to need some level of institutional long term care. Community pharmacies are positioned to delay this need by supporting medication management. There are potential mechanisms for pharmacists to deliver long term care at home (Home LTC) services and bill insurers for services that may delay the transition to a higher level of care.